Challenges to human papillomavirus vaccination among young girls in Morocco: A national cross-sectional study - Touria Essayagh; Meriem Essayagh; Housnia Slibani; Soukayna El Hachimi; Kaoutar Nmila; Khaoula Addakiri; Rehmatullah Zadran; Sanah Essayagh (PLoS ONE, 2026)
Background The human papillomavirus (HPV) vaccine helps significantly reduce the incidence of cervical cancer. However, in many countries, its adoption remains limited. In this context, our study aimed to measure the prevalence of HPV vaccination hesitancy among young girls and to identify its associated risk factors. Methods From 10 th April to 30 th June 2025, a cross-sectional survey was conducted in Morocco among girls aged 11–14 attending middle school. Face-to-face interviews gathered sociodemographic data, HPV knowledge, and vaccination attitudes. Multivariate logistic regression identified risk variables for vaccine hesitancy. Results A total of 1,836 participants were collected with a mean age of 13.0 ± 0.8 years. The percentage of vaccine hesitancy reached 88.8%. The main risk factors were unvaccinated pairs (AOR = 11.78; CI [7.67–18.0]), paternal illiteracy (AOR = 7.67; [1.99–29.55]), low recommendation of the vaccine by health personnel (AOR = 4.14; [2.44–7.02]), belief that the vaccine promotes sexual activity (AOR = 3.10; [2.01–4.79]), insufficient knowledge of the target population (AOR = 2.51; [1.63–3.85]), perception of adverse effects (AOR = 1.97; [1.31–2.98]), insufficient knowledge of the number of doses required (AOR = 1.76; [1.06–2.92]), fear of vaccination (AOR = 1.71; [1.14–2.58]), fear of regretting vaccination (AOR = 1.55; [1.02–2.36]), and age (AOR = 1.34; [1.06–1.69]). Conclusion HPV vaccination hesitancy remains high and is shaped by social, educational, and cultural factors. These findings underscore the need for targeted educational initiatives and increased awareness among healthcare professionals. Integrating vaccination into school health programs may help improve uptake.